Conversation - Nolasco, Rob.; Arthur, Lois. (Oxford : New York : Oxford University Press, 1987)
This very popular series gives teachers practical advice and guidance, together with resource ideas and materials for the classroom.
Includes bibliography(p. 145-148).
Keywords: Englisch; Englischunterricht; Fremdsprachenunterricht